EDUCATION ON HYPERTENSION DIET AND THE USE OF ROSELLA FLOWERS (Hibiscus Sabdariffa) AS ADDITIONAL FOOD FOR HYPERTENSION PATIENTS - Shobirin, Gilang Akbar; Putri, Diah Pitaloka; Luthfiah, Nita Hasna; Agrisdian, Zerly; Pratiwi, Widhya Endah; Kurniawan, Vendi Eko (Journal of Indonesian Public Health Service, 2024)
Currently, hypertension is still a major problem for the elderly because its prevalence is increasing. Roselle flowers (Hibiscus sabdariffa) can be used as one of the main ingredients in making snacks (pudding) because roselle flowers have good nutritional content, including antioxidants. The implementation of this community service activity aims to provide education on the hypertension diet and the use of roselle flowers (Hibiscus sabdariffa) as an alternative snack for hypertension sufferers. This activity was carried out on February 25, 2024 at Perumda Candimulyo, Jombang Regency. The target for carrying out activities is the elderly with a total of 23 people. A series of community service activities, including health and anthropometric examinations, hypertension diet education, education on making and distributing roselle (Hibiscus sabdariffa) pudding. The method for implementing this activity is health education using the group discussion method. The media used in delivering this activity is leaflets. Community service activities take place in an orderly and smooth manner. By carrying out this activity, it is hoped that the elderly can adopt a healthy eating pattern so they can control blood pressure while at home.